Manufacturing and mechanical performance of novel epoxy resin matrix carbon fiber reinforced damping composites. (15th January 2021) - Zheng, Changsheng; Duan, Fenghai; Liang, Sen
Abstract: In order to improve mechanical performance and interfacial bonding property of traditional sandwich damping composites, a novel epoxy resin matrix carbon fiber reinforced composite with viscoelastic sandwich layers was investigated via co-curing technology. The viscoelastic sandwich layers were developed by designing their formula. The normal curing time, tensile strength and loss factor of designed viscoelastic material reached 70 min, 22.71 MPa and 1.07 respectively. The mechanical properties and damping characteristics of sandwich composite were determined by static mechanical experiment and single cantilever beam vibration experiment. The tensile strength and flexural strength of control one were 890.4 MPa and 756.5 MPa respectively. While addition of 0.1 mm thickness of damping film into laminates could result in a decline of 1.34% in tensile strength and an augment of 1.30% in flexural strength of composites. The loss factor of damping composite structure was obtained by least square method. The loss factor and interfacial shear stress of specimen 2 were 6.84% and 9.65 MPa, approximately 25.74% and 179.82% higher than that of reference. The experimental results exhibit that the work promotes the development of functional composites in field of vibration and noise reduction.